Development of a Receiver Evaluation System Using 30 kWth Point Concentration Solar Simulator. (May 2015) - Nakakura, M.; Ohtake, M.; Matsubara, K.; Yoshida, K.; Cho, H.S.; Kodama, T.; Gokon, N.
Abstract: The point-concentration receiver evaluation system was developed using the world class 30 kWth light source of 19 arc xenon lamps. The system comprises of a receiver unit, heat exchanger, blower, chiller and light source. Precise measurement of the thermal power absorbed by air was performed by the enthalpy rise of the coolant water and that of the exhausted air. The experimental test was performed using silicon carbide honeycomb in order to achieve a high air temperature of 560 °C. The efficiency of the receiver, based on the power of the aperture, was 40% to 80%. A three-dimensional simulation based on the dual cell approach was made to reveal detailed information of the flow and temperature fields. This successfully reproduced the thermal nonequilibrium between the solid and fluid parts of the receiver. The air exit temperature and efficiency of the numerical simulation were consistent with that determined experimentally. Air was suctioned from the broad space above the receiver top surface. The adopted simulation model with the free stream was confirmed to be essential for evaluating an open loop receiver.